Polarized radiation from the spreading layer of weakly magnetized neutron stars - Bobrikova, Anna; Poutanen, Juri; Loktev, Vladislav (EDP Sciences, 2025)
Observations show that the X-ray emission of the accreting weakly magnetized neutron stars is polarized. We developed a theoretical model for polarized radiation from the spreading layer, which is the extension of the accretion flow boundary layer onto the neutron star surface. We calculated the Stokes parameters of the radiation and accounted for relativistic aberration and gravitational light bending in the Schwarzschild metric. We show that regardless of the geometry, the polarization degree of the spreading layer does not exceed 1.5%. Our results have implications with regard to the understanding of the X-ray polarization from weakly magnetized neutron stars observed with the Imaging X-ray Polarimetry Explorer and the future enhanced X-ray Timing and Polarimetry mission.